Tick diversity and molecular detection of Anaplasma, Babesia, and Theileria from Khao Kheow open zoo, Chonburi Province, Thailand - Sri-in, Chalida; Thongmeesee, Kritsada; Wechtaisong, Wittawat; Yurayart, Nichapat; Rittisornthanoo, Ganyawee; Akarapas, Chatlada; Bunphungbaramee, Natcha; Sipraya, Natthanicha; Riana, Elizabeth; Bui, Thuong Thi Huyen; Kamkong, Patchana; Maikaew, Umaporn; et al. (Frontiers in Veterinary Science, 2024)
Ticks are obligate blood-feeding ectoparasites notorious for their role as vectors for various pathogens, posing health risks to pets, livestock, wildlife, and humans. Wildlife also notably serves as reservoir hosts for tick-borne pathogens and plays a pivotal role in the maintenance and dissemination of these pathogenic agents within ecosystems. This study investigated the diversity of ticks and pathogens in wildlife and their habitat by examining ticks collected at Khao Kheow Open Zoo, Chonburi Province, Thailand. Tick samples were collected for one year from March 2021 to March 2022 by vegetation dragging and direct sampling from wildlife. A total of 10,436 ticks or 449 tick pools (1-50 ticks per pool) underwent screening for pathogen presence through conventional PCR and DNA sequencing. Out of the 298 samples (66.37%) where bacteria and protozoa were detected, encompassing 8,144 ticks at all stages, 114 positive samples from the PCR screenings were specifically chosen for detailed nucleotide sequencing and comprehensive analysis. Four species of ticks were conclusively identified through the application of PCR, namely, Rhipicephalus microplus, Dermacentor auratus, Haemaphysalis lagrangei, and Haemaphysalis wellingtoni. The highest infection rate recorded was for Anaplasma spp. at 55.23% (248/449), followed by Babesia spp. and Theileria spp. at 29.62% (133/449) and 16.26% (73/449), respectively. Among bacteria identified, three Anaplasma genotypes were closely related to an unidentified Anaplasma spp., A. phagocytophilum, and A. bovis. Among protozoa, only an unidentified Babesia spp. was found, whereas two Theileria genotypes found were closely related to unidentified Theileria spp. and T. equi. Significantly, our findings revealed coinfection with Anaplasma spp., Theileria spp., and Babesia spp. While blood samples from wildlife were not specifically collected to assess infection in this study, the data on the presence of various pathogens in ticks observed can serve as valuable indicators to assess the health status of wildlife populations and to monitor disease dynamics. The findings could be valuable in developing programs for the treatment, prevention, and control of tick-borne illnesses in this area. However, additional research is required to determine the ticks’ ability to transmit these pathogens and enhance the current understanding of the relationship among pathogens, ticks, and hosts.